2011
DOI: 10.1186/1741-7007-9-64
|View full text |Cite
|
Sign up to set email alerts
|

Double-strand break repair processes drive evolution of the mitochondrial genome in Arabidopsis

Abstract: BackgroundThe mitochondrial genome of higher plants is unusually dynamic, with recombination and nonhomologous end-joining (NHEJ) activities producing variability in size and organization. Plant mitochondrial DNA also generally displays much lower nucleotide substitution rates than mammalian or yeast systems. Arabidopsis displays these features and expedites characterization of the mitochondrial recombination surveillance gene MSH1 (MutS 1 homolog), lending itself to detailed study of de novo mitochondrial gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
306
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 215 publications
(320 citation statements)
references
References 46 publications
12
306
2
Order By: Relevance
“…Still, the rearranged region integrated into the chimeric mitochondrial genomes by homologous recombination preserving either the CMS or fertile mtDNA structure. Thus, nonhomologous end joining, the driving force behind mtDNA rearrangement during evolution, is not involved in the formation of mosaic mtDNAs (31,32). The rearranged mitochondrial genomes were stable for at least three seed generations.…”
Section: Identification Of a Tentative Cms Gene In Recombinant Mitochmentioning
confidence: 84%
“…Still, the rearranged region integrated into the chimeric mitochondrial genomes by homologous recombination preserving either the CMS or fertile mtDNA structure. Thus, nonhomologous end joining, the driving force behind mtDNA rearrangement during evolution, is not involved in the formation of mosaic mtDNAs (31,32). The rearranged mitochondrial genomes were stable for at least three seed generations.…”
Section: Identification Of a Tentative Cms Gene In Recombinant Mitochmentioning
confidence: 84%
“…This variation at the level of entire chromosomes is in striking contrast to the overall pattern of structural conservation in the set of shared chromosomes. The lack of inversions and rearrangements is highly unusual for angiosperm mitochondrial genomes, which are often structurally dynamic even within species (27)(28)(29)(30). This difference is likely caused by a reduced rate of intragenomic recombination between small repeats in S. noctiflora mtDNA (22).…”
Section: Discussionmentioning
confidence: 99%
“…As in this study, the identification of multichromosomal structures in angiosperms has been based almost exclusively on mapping/ sequencing (21-23), but, in some other cases, sequence data have been supplemented with electrophoretic separation of chromosomes and electron microscopy-based observations (11,12,14,15,17,18,20,45,46). To date, the only direct characterization of chromosomal structure in an angiosperm multichromosomal mitochondrial genome was performed in Silene vulgaris (26)(27)(28)(29)(30). In this case, a Southern blot analysis of the smallest (∼5 kb) mitochondrial chromosome confirmed the existence of the predicted circular molecules but found that most of the DNA was present in multimeric forms that varied in susceptibility to exonuclease digestion, indicating diversity in molecular size and structure.…”
Section: Are S Noctiflora Mitochondrial Chromosomes Being Gained or mentioning
confidence: 99%
See 1 more Smart Citation
“…Disruption of MSH1 enhances recombination at 47 pairs of repeated sequences in the mitochondrial genome of Arabidopsis (Arabidopsis thaliana; Shedge et al, 2007;Arrieta-Montiel et al, 2009;Davila et al, 2011) and gives rise to cytoplasmic male sterility in tomato (Solanum lycopersicum ) and tobacco (Nicotiana tabacum; Sandhu et al, 2007). Within the chloroplast, disruption of MSH1 results in low-frequency DNA rearrangements mediated by recombination, together with altered redox properties of the cell and variegation of the plant .…”
mentioning
confidence: 99%